The Effect of Current Ratio, Debt to Asset Ratio, Debt to Equity Ratio and Net Profit Margin on Return on Equity in the Food and Beverage Industry Companies Listed on IDX for the 2016 – 2020 - Friska Darnawaty Sitorus; Ayusari Br Sinaga; Innemyus Laia; Cathlin Tandy (Budapest International Research and Critics University, 2022)
This study aims to determine and examine the effect of Current Ratio on ROE, the effect of Debt To Asset Ratio on ROE, Debt To Equity Ratio and net profit margin on ROE in manufacturing companies in the food and beverage industry sub-sector listed on the Indonesia Stock Exchange for the period 2016 – 2020. Quantity method ( Quantity method) is used in this study which is a technique that utilizes mathematical models in the form of numbers. The population of food and beverage companies is 26 companies. The selected sample amounted to 11 companies selected through purposive sampling.Data were collected through documentation techniques and utilizing secondary data as a source of research data.Based on the results of the T test and F test in this study, all independent variables affect the Return On Equity of food and beverage companies listed on the IDX simultaneously. Current Ratio (CR) to Return On Equity (ROE) has a positive and significant effect. Debt To Asset Ratio (DAR) to Return On Equity (ROE) has a positive but not significant effect. Debt To Equity Ratio (DER) to Return On Equity (ROE) has a negative and insignificant effect. And Net Profit Margin (NPM) has a significant and positive effect on Return On Equity (ROE) in food and beverage companies listed on the IDX for the 2016-2020 period.